2013
DOI: 10.1603/me13027
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of the 14.5 Antibacterial NlpC/P60-Like <I>Dermatophagoides pteronyssinus</I> Protein in <I>Dermatophagoides farinae</I> (Acari: Pyroglyphidae)

Abstract: House dust mites produce antibacterial proteins suppressing bacterial growth. The 14.5-kDa bacteriolytic protein (UniProtKB Q8MWR6) has been known in Dermatophagoides pteronyssinus Trouessart. We have applied polymerase chain reaction and reverse transcription-PCR to detect a homologous gene sequence coding for a Q8MWR6-related protein in Dermatophagoides farinae (Hughes) using genomic DNA and total RNA, respectively. The resulting PCR product of expected size, 243 bp, was obtained from both Dermatophagoides s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…S12 C , Supplementary Material online). This peptidoglycan endopeptidase has been reported and explored in several astigmatic mites ( Mathaba et al 2002 ; Erban et al 2013 ; Chan et al 2015 ; Tang et al 2015 , 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S12 C , Supplementary Material online). This peptidoglycan endopeptidase has been reported and explored in several astigmatic mites ( Mathaba et al 2002 ; Erban et al 2013 ; Chan et al 2015 ; Tang et al 2015 , 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In astigmatic mites, except for the HGT peptidoglycan endopeptidase, which was identified and explored ( Mathaba et al 2002 ; Erban et al 2013 ; Chan et al 2015 ; Tang et al 2015 , 2017 ), very few HGT events were reported previously. UGTs, chitinases, and other genes were reported as HGT genes in spider mites ( Ahn et al 2014 ; Wybouw et al 2018 ; Snoeck et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The percent GC contents of the nucleotide sequences were 38.9, 39.3, 38.5, 36.7, 41.9 and 58, for lytFM , lytFM1 , lytFM2 , D. farinae , P. ovis and B. tropicalis homologues, respectively. Two conservative polymorphisms were detected when the full‐length [19] and partial [26] D. farinae sequences were compared, namely Lys for Arg at residue position 29 and Ile for Leu at position 45 (mature D. pteronyssinus numbering, Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…6 and Table S31). Except the peptidoglycan endopeptidase reported in both D. farinae and D. pteronyssinus [46][47][48] , none of other HGT events was reported in astigmatic mites previously. UGTs, chitinase and other genes were reported as HGT genes in spider mite [58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the peptidoglycan endopeptidase was tandemly duplicated in both P. ovis and T. putrescentiae, while decayed (complete deletion) in S. scabiei. This peptidoglycan endopeptidase was reported in both D. farinae and D. pteronyssinus [46][47][48] . These HGT-gained lytic enzymes for fungal and bacterial cell wall are considered to play vital roles in the digestive functions of astigmatic mites, particularly house dust mites, D. farinae and D. pteronyssinus feeding on human skin flakes colonized by microbes including fungi and bacteria 10,49,50 .…”
Section: Lysis Of Bacterial Cell Wallmentioning
confidence: 94%